Chemotherapy-induced peripheral neuropathy and its determinants among adult cancer patients on chemotherapy in northwest Ethiopia oncology centers, 2022 - Habtie, Tesfaye Engdaw; Abate, Melsew Dagne; Abebe, Gebremeskel Kibret; Wolie, Zenaw Tessema; Alamaw, Addis Wondmagegn; Mitiku, Haymanot Zeleke (Frontiers in Oncology, 2024)
IntroductionPeripheral neuropathy is a nerve disorder that causes pain, numbness, and tingling in different parts of the body. It is a major and common clinical problem associated with several chemotherapeutic medications frequently used in cancer treatment, with prevalence rates ranging from 19% to 85%. To the best of the authors’ knowledge, there is a lack of data on the magnitude and determinants of chemotherapy-induced peripheral neuropathy in Ethiopia.ObjectiveThis study aimed to assess the magnitude and associated factors of chemotherapy-induced peripheral neuropathy among adult cancer patients undergoing chemotherapy in northwest Ethiopia oncology centers in 2022.MethodAn institutional-based cross-sectional study was conducted on 406 eligible adult cancer patients undergoing chemotherapy in northwest Ethiopia oncology centers, between May and July 2022.ResultsOut of 406 adult cancer patients included in the study, 54.4% had peripheral neuropathy. The stage of cancer (AOR = 4.36 [95% CI: 1.76; 10.8]), comorbidity (AOR = 2.74 [95% CI: 1.28; 5.83]), drug regimen (AOR = 2.99 [95% CI: 1.36; 6.54]), and cycle of therapy (AOR = 4.00 [CI: 1.67; 9.65]) were significantly associated with the magnitude of chemotherapy-induced peripheral neuropathy.ConclusionChemotherapy-induced peripheral neuropathy is a common adverse event among Ethiopian cancer patients treated with various chemotherapeutic drugs. Therefore, it is necessary to establish more effective diagnostic methods and incorporate validated assessment tools, such as the European Organization for Research and Treatment of Cancer tools, either alone or in combination with other clinical instruments, into the routine evaluation of all patients receiving chemotherapeutic drug.